Perbandingan Keakuratan Model Arus Kas Metoda Langsung dan Tidak Langsung dalam Memprediksi Arus Kas dan Deviden Masa Depan - Handri Thiono (The Indonesian Journal of Accounting Research, 2013)
The objective of the study was to examine the ability of direct and indirect method information in predicting future cash flow and dividend. This study evaluated FASB's statements in SFAS 95 and IAI's statements in PSAK No. 2, that the direct method provided more useful information in predicting future cash flow than indirect method. Panel data regression models were developed. The study evaluated two cash flow and dividend prediction models, that employed cash inflows from operating activities, cash outflows for operating activities, net income, and accrual. The sample of this study was manufacturing companies listed in Jakarta Stock Exchange within the period of 1999-2004. The data was collected using purposive sampling method. The amount of the sample was 35 companies for cash flow prediction models, and 25 companies for dividend prediction models.The results of this study showed that a combination of cash inflows and cash outflows outperform net income and accrual in predicting future cash flow. However, the evidence showed that direct method model did not outperform indirect method model in predicting future dividend. The empirical results supported the FASB's statements, that direct method provided useful information in predicting future cash flow than indirect method.